Tips to Improve Performance - Julian, Julian; Farida Ferine, Kiki (PT. Multidisciplinary Press Indonesia, 2024)
HR is one component of the organizational system, which ironically is also one component of the employment management system which prioritizes competition in achieving work results, both in individual and organizational environments. Human resources (HR) are a crucial element. The results of this research are as follows: Teamwork has a positive and significant effect on employee performance with an original sample value of 0.531 and a p value of 0.000. Work Quality has a positive and significant effect on Teamwork with an original sample value of 0.325 and a p value of 0.000. Work Quality has a positive and insignificant effect with an original sample value of 0.123 and a p value of 0.127. Organizational Citizenship Behavior has a positive and significant effect on Teamwork with an original sample value of 0.424 and a p value of 0.000. Organizational Citizenship Behavior has a positive and significant effect on Employee Performance with an original sample value of 0.188 and a p value of 0.026. Training has a positive and significant effect on Teamwork with an original sample value of 0.236 and a p value of 0.021. Training has a positive and insignificant effect on employee performance with an original sample value of 0.136 and a p value of 0.077. Work Quality has a positive and significant effect on Employee Performance through Teamwork with an original sample value of 0.173 and a p value of 0.003. Organizational Citizenship Behavior has a positive and significant effect on Employee Performance through Teamwork with an original sample value of 0.225 and a p value of 0.002. Training has a positive and significant effect on employee performance through teamwork with an original sample value of 0.125 and a p value of 0.035.